Micro-sized erosions in a nanofilled composite after repeated acidic beverage exposures: consequences of clusters dislodgments (Journal of Applied Oral Science, 2014)
Objective: To evaluate the hardness (KHN), color stability (DE), and superficial micromorphology of two categories of composites after immersion in either distilled water or grape juice for up to 45 days. MATERIAL AND METHODS: Cylindrical specimens (6 mm diameter x 2 mm thick) were obtained according to the factors: composite [Opallis (FGM) and Filtek Z350XT (3M ESPE)]; immersion solution (distilled water and grape juice); and evaluation time: 24 h and 7, 14, 21, 28, and 45 days. After photoactivation, the specimens were stored at 37ºC for 24 h. KHN (50 g/15 s) and ΔE were then repeatedly assessed according to the immersion solutions. Data were analyzed (three-way ANOVA/Tukey's test). Scanning electron microscopy (SEM) topographic analysis was also performed. RESULTS: In general, KHN of both composites reduced after 24 h, irrespective of the immersion solution and time. A significantly lower KHN was noted for Opallis compared with Filtek Z350XT in all parameters. An increase in ΔE over time was noted for both composites, irrespective of the immersion solution. Significantly higher ΔE was noted for Filtek Z350XT immersed in grape juice compared with Opallis, regardless of the evaluation time. The grape juice caused significantly higher DE compared with water in all periods. SEM analysis showed eroded areas for Filtek Z350XT but not for Opallis. CONCLUSIONS: The compositions and immersion solutions influence the composite hardness and the color stability. In spite of the higher hardness, the nanofilled composite is more susceptible to color change than the microhybrid when immersed in an acidic dyed solution.